Literatur Review: Efek Samping Penggunaan Obat Hipertensi - Sekar Anastry Putri; Dwi Aulia Ramdini; Afriyani; M. Fitra Wardhana (CV. Jasa Sukses Abadi, 2023)
Hypertension is a major risk factor for cardiovascular disease. Hypertension also has another term, namely